RISK FACTORS OF SURGICAL SITE INFECTION IN EMERGENCY OPEN ABDOMINAL SURGERY - KHIAL, M; REHMAN , SU; AKBAR, S; ANWAR, A; HABIB, K; ASIYA, . (Biological and Clinical Sciences Research Journal, 2024)
Surgical site infections (SSIs) are major complications following emergency open abdominal surgeries. These risks contribute to high morbidity, mortality, prolonged hospital stay and increased length of ICU. Objective: This study sought to determine and analyze the risk factors associated with SSIs among patients undergoing emergency open abdominal surgeries. Methods: This observational study was conducted at the Department of Surgery, Hayatabad Medical Complex, Peshawar, from 1st February 2024 to 31st July 2024. Male and female patients who had emergency open abdominal surgery and were aged 18 years or older without pre-existing infection, and immune compromise at the time of surgery. The study excluded patients undergoing elective abdominal surgery, those with incomplete medical records, and participants less than 18 years of age. Results: A total of 196 patients were enrolled in the study, 115 (58.7%) of whom were male and 81(41.3%) female. The mean age of the patients in SSIs was 55.4 years and compared to those without SSIs was 50.8 years. Obesity (BMI ≥ 30) among SSI patients (52.4% vs. 22.7%, p = 0.001). SSI patients had a significantly longer hospital stay (mean 15.8 days vs. 9.3 days, P < 0.001) and were more likely to be admitted to the ICU (73.8% vs. 33.8%, P < 0.001). Conclusion: This study highlights the multifactorial aetiology of SSIs in emergency open abdominal surgery, from preoperative to post-operative patient-related as well as procedural factors. It is critical to have a thorough understanding of these risk variables to implement focused prevention strategies and lower the incidence of SSI-related events.